Demographics, Digitalization, and Disclosure: Key Drivers of Financial Report Quality in Papua’s Local Government - Warokka, Ari; Aqmar, Aina Zatil; Warokka, Vetaroy (Universitas Terbuka, 2025)
Under regional autonomy, transparent and high-quality financial reporting, including robust disclosure, is essential for Indonesian local governments. Despite improved audit ratings, Papua Province still struggles with financial report quality and full disclosure, as indicated by recurring audit findings. This study investigates the influence of human resource (HR) competence, internal control systems, government accounting standards, and information technology on the quality of financial reports within the Papua Provincial Government. In addition, it explores the moderating role of demographic factors (specifically age and education) in the relationship between HR competence and information technology with financial reporting quality. Data were collected through a structured questionnaire distributed to 210 employees across various local government work units in Papua Province. The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings reveal that HR competence, government accounting standards, and the use of information technology significantly enhance the quality of financial reports. Conversely, the internal control system does not exhibit a significant effect. Furthermore, age and education significantly moderate the relationship between information technology and financial report quality but do not significantly moderate the relationship between HR competence and financial report quality. These results underscore the importance of technological adaptation and tailored human resource strategies in improving public sector financial transparency.